Flutter Suppression of Wind Turbine Blade based on Adaptive Fuzzy Sliding Mode Control. Issue 1 (1st January 2022) - Wang, Yingbo; Sun, Changle; Sun, Haipeng; Zhang, Xiaolin; Liu, Tingrui
Abstract: Aiming at the divergent unstable vibration of wind turbine blades, an adaptive fuzzy sliding mode control algorithm based on sliding mode control is proposed to solve the classic flutter fracture failure problem of blades. The structural model is a typical blade section model based on spring-mass-damper, and the aeroelastic equation is obtained by combining the steady aerodynamic model suitable for pure pitch motion. The adaptive fuzzy sliding mode controller gives the pitch signal, and the second-order pitch actuator performs the pitch action to suppress flutter. The saturation function with variable boundary layer thickness is used instead of symbolic function, and the approach rate parameter is adjusted appropriately by fuzzy rules, so as to realize variable-parameter adaptive fuzzy sliding mode control. Simulation results show that, compared with the traditional sliding mode controller, the proposed control algorithm can not only suppress the classical flutter, but also effectively reduce the amplitude and frequency of chattering, and has good robustness.